The role of nurses' professional values during the COVID-19 crisis - González-Pando, David (Nursing ethics, 2022)
Background:The COVID-19 pandemic has produced high stress in nurses, affecting their professional quality of life. Different variables affect psychological stress response and professional quality of life. In this context, the role of professional values represents an interesting object of research.Objectives:To analyze the relationship between professional values, perceived stress, and professional quality of life among nurses during the COVID-19 crisis.Research design, participants, and research context:Descriptive cross-sectional study. Participants were 439 registered nurses from the public health system. Perceived stress, professional quality of life, and professional values were evaluated by using measuring instruments adapted and validated in the geographic context of research. Data were collected online in December 2020 during the second wave of the COVID-19 pandemic in Spain.Ethical considerations:This study was approved by the Ethics Committee on Clinical Research of the Principality of Asturias.Findings:Within professional values, ethics obtained higher scores showing the primacy of ethical values among nurses. Moderate correlations between ethics, mastery, expertise, and compassion satisfaction were found. Frontline nurses informed high perceived stress. The correlations between professional values and compassion satisfaction were higher in non-frontline nurses. A moderate negative correlation between perceived stress and compassion satisfaction was found in both groups, which implies that the higher the stress, the lower the satisfaction in the helping relationship.Conclusion:Professional values positively influence compassion satisfaction during the COVID-19 pandemic. Compassion satisfaction presents a negative correlation with fatigue compassion and burnout in frontline and non-frontline nurses. Given the functionality of values both to guide clinical practice professionally and ethically, and prevent dissatisfaction with one’s professional quality of life by reinforcing compassion satisfaction, it is necessary to reinforce them with an intensive and cross-sectional learning during the university training.